2014
DOI: 10.3390/ijerph110505155
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution Patterns in Environmental Factors, Chlorophyll-a and Microcystins in a Large Shallow Lake, Lake Taihu, China

Abstract: The spatio-temporal distribution of environmental factors, chlorophyll-a (Chl-a), and microcystins (MCs) in a shallow lake, Lake Taihu (China), were investigated from 2009 to 2011 on a monthly basis at nine sampling stations. The annual mean concentration ranges of total nitrogen (TN), total phosphorus (TP), Chl-a, MC-LR and MC-RR were 0.17–10.53 mg/L, 0.027–0.581 mg/L, 0.10–129.75 µg/L, 0.013–2.019 µg/L and 0.002–0.794 µg/L, respectively. The average TN, ammonium (NH4+) and TP concentrations in Meiliang Bay d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Our results indicated that cyanobacteria biovolume, Chl-a and DOC had a positive effect, and nitrate, nitrite and DIC had a negative effect on MC-YR production. While some studies have focused on MC-LR and MC-RR [ 48 , 49 , 50 , 61 , 65 ], there has been much less focus on MC-YR. Given that MC-YR is almost as toxic as MC-LR according to toxicity equivalent factors (TEF) [ 66 , 67 ], more attention is warranted to better understand how environmental factors influence its production.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that cyanobacteria biovolume, Chl-a and DOC had a positive effect, and nitrate, nitrite and DIC had a negative effect on MC-YR production. While some studies have focused on MC-LR and MC-RR [ 48 , 49 , 50 , 61 , 65 ], there has been much less focus on MC-YR. Given that MC-YR is almost as toxic as MC-LR according to toxicity equivalent factors (TEF) [ 66 , 67 ], more attention is warranted to better understand how environmental factors influence its production.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of eutrophication level in the rearing water, cyanobacteria are easy to multiply, which not only pollutes the water quality, but also releases a large amount of cyanotoxins, threatening the health and food safety of shrimp (Magalhães et al, 2003;Pham and Utsumi, 2018). Microcystins (MCs) are one of the most common and highly toxic cyanotoxins, the concentration of which in cyanobacterial bloom ponds can reach 0.1-10 μg/l (Ye et al, 2014;Li et al, 2016). Microcystin-LR (MC-LR) is considered to be the most common and widely studied type of MCs, which are encountered in freshwater systems, estuarine and marine environments (Anderson et al, 1993;Ramos et al, 2005;Miller et al, 2010;Preece et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of Microcystis across the year was consistent with the strong acclimation of this species to different water temperatures [ 51 , 52 ]. In terms of the life-cycle of Microcystis , early studies proposed that this cyanobacterium overwinters in the sediment [ 53 , 54 , 55 , 56 ]. Recently, in a shallow eutrophic lake, a Microcystis bloom was found to persist in winter although at a relatively lower abundance than in summer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%